Conversaciones - Rubenstein, David M. (BookaVivo, 2022)
WHAT MAKES GREAT LEADERS STAND OUT? Learn about the guiding principles and philosophies of Bill Gates, Jeff Bezos, Ruth Bader Ginsburg, Warren Buffett, Oprah Winfrey, and many other famous people through insightful conversations about their lives and career paths. Learn from the top CEOs, presidents, founders, and leaders from the worlds of finance, technology, entertainment, sports, and politics. Discover how each of them has been forged and how they have turned small ideas into ideas that have defined an entire generation.